Distribution, genetic polymorphism and genotype prediction of Rhesus blood group antigens among the Kurdish population of Zakho, Kurdistan Region, Iraq - Shakir A. Zebari; Sawer S. Ahmed; Ibrahim A. Naqid; Shivan U. Muhammed; Abdullah S. Muhi (PLoS ONE, 2026)
The Rhesus blood group system exhibits significant polymorphism, with diverse antigen distributions across populations. This study investigates the antigenic profile, haplotype frequencies, and genotype predictions in a cohort from Zakho, Kurdistan Region, Iraq, which is crucial for transfusion medicine and genetic studies. A prospective cross-sectional analysis was performed on 1,000 Kurdish individuals at Zakho Emergency Teaching Hospital. Blood samples were phenotyped for Rh (D, C, c, E, e) antigens. Haplotype assignments were made using Fisher-Race terminology, and probable genotypes were calculated based on allele frequencies and Wiener nomenclature. The most common Rhesus blood antigens are Rh(e) (95%), Rh(D) (91.9%), Rh(C) (76%), and Rh(c) (68%). Rh(E) is found in 25.8% of individuals, while only 8.1% are Rh(D) negative. Among the Rh(D) positive population, the most frequent phenotype/haplotype and presumed genotype was DCe ( DCe/DCe, R1R1 ) at 31.4%, followed by DCce ( DCe/dce, R1r ) at 29.3%, and DCcEe ( DCe/DcE, R1R1 ) at 13.8%. The dce phenotype ( dce/dce, rr , in 7.2%) was the most common among Rh(D) negative individuals. No significant differences were observed between sexes. This study reveals that DCe, DCce, and DCcEe are prevalent phenotypes among Rh(D) positive individuals, whereas the dce haplotype predominates among Rh(D) negative individuals. The Rhesus phenotype/genotype aligns with Kurdish and Arab groups in Iraq and shows partial resemblance to Western European, Indian, and Iranian populations, but significantly differs from African-American populations, except for the dce phenotype ( dce/dce, rr) . These findings are crucial for blood transfusion strategies, donor selection, maternal and fetal health, the prevention of Rh incompatibilities, and genetic research in the region.